Antimicrobial-Impregnated Dressing Combined with Negative-Pressure Wound Therapy Increases Split-Thickness Skin Graft Engraftment. (January 2015) - Wu, Cheng-Chun; Chew, Khong-Yik; Chen, Chien-Chang; Kuo, Yur-Ren
ABSTRACT OBJECTIVE: Immobilization and adequate surface contact to wounds are critical for skin graft take. Techniques such as the tie-over dressing, cotton bolster, and vacuum-assisted closure are used to address this, but each has its limitations. This study is designed to assess the effect of antimicrobial-impregnated dressing (AMD) combined with negative-pressure wound therapy (NPWT) on skin graft survival. DESIGN: Retrospective case-control study PARTICIPANTS: Patients with chronic or contaminated wounds treated with split-thickness skin graft. A broad spectrum of wounds was included, from causes such as trauma, burns, chronic diabetic ulcers, and infection. INTERVENTIONS: Antimicrobial-impregnated dressing, which contains 0.2% polyhexamethylene biguanide, with NPWT MAIN OUTCOME MEASURE: Success of skin graft MAIN RESULTS: In the AMD group, all skin grafts achieved 100% take without secondary intervention. No infection or graft failure was observed in any patients, and no complications, such as hematoma or seroma formation, were noted, although in the control group partial loss of skin grafts was noted in 3 patients. Infection and inadequate immobilization were thought to be the main reasons. There were no hematoma or seroma formations in the control group. CONCLUSION: Use of an AMD dressing with NPWT after split-thickness skin grafting can be an effective method to ensure good graft to wound contact and enhances skin graft take in chronic and contaminated wounds.